AKTIVITAS ANTIOKSIDAN DAN TABIR SURYA FRAKSI FENOLIK DARI LIMBAH TONGKOL JAGUNG (Zea mays L.) - Wungkana, Injilia (UNIVERSITAS SAM RATULANGI, 2013)
The purpose of this study was to determine the antioxidant activity and sunscreens of phenolicfraction of waste corn cobs (Zea mays L.). Corn cob that has been extracted using the winddried reflux for 2 hours. Furthermore corncob extract liquid successively fractionated using nhexane, ethyl acetate, butanol and ethanol 70%. Analysis of total phenolic content, freeradical scavengers activity determination using DPPH (1,1-diphenyl-2-picrylhidrazil) andsunscreen effectiveness by determining in vitro SPF values by spectrophotometric method.The results of this study indicate that the ethyl acetate fraction has a higher content of totalphenolic fraction followed by butanol, 70% ethanol and n-hexane. Total phenolic content of arow is 96.42;35.81;19.18 and 11.52 mg/mL. Ethyl acetate fraction also has a free-radicalscavengers activity is higher than the other factions. The research concludes phenolic fractionof ethyl acetate can act as an antioxidant as well as a sunscreen with the highest SPF valuefollowed fraction 70% ethanol, n-hexane and butanol. The research obtained that phenolicfraction of waste corn cob as antioxidant and sunscreenKey words : Antioxidant, Phenolic fraction, Sunscreen, Waste Corn Cob